2014
DOI: 10.1186/1471-2393-14-255
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of antenatal care and its relationship with low birth weight in Botucatu, São Paulo, Brazil: a case-control study

Abstract: BackgroundBirth weight reflects gestational conditions and development during the fetal period. Low birth weight (LBW) may be associated with antenatal care (ANC) adequacy and quality. The purpose of this study was to analyze ANC adequacy and its relationship with LBW in the Unified Health System in Brazil.MethodsA case-control study was conducted in Botucatu, São Paulo, Brazil, 2004 to 2008. Data were collected from secondary sources (the Live Birth Certificate), and primary sources (the official medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
4
24
0
5
Order By: Relevance
“…Those who had poor care were more likely to suffer from preterm birth, low birth weight, still birth, low APGAR score, post term birth, induction of labor, augmentation of labor, and dystocia. This result is similar to that obtained in similar studies, 13,27,38 however most studies compared adequacy of care and one or two adverse outcomes. Regina and colleagues 38 showed an association between low birth weight and inadequate care but did not find any association between poor care and the other adverse outcomes.…”
supporting
confidence: 90%
“…Those who had poor care were more likely to suffer from preterm birth, low birth weight, still birth, low APGAR score, post term birth, induction of labor, augmentation of labor, and dystocia. This result is similar to that obtained in similar studies, 13,27,38 however most studies compared adequacy of care and one or two adverse outcomes. Regina and colleagues 38 showed an association between low birth weight and inadequate care but did not find any association between poor care and the other adverse outcomes.…”
supporting
confidence: 90%
“…[12] However, da Fonseca et al (2014) found no association between adequacy of ANC and LBW. [13] Although antenatal care is one of the most effective ways of reducing maternal and perinatal mortality and morbidity, this study found contradictory results in LBW pregnancy. Complete antenatal care increased the risk of having a LBW baby.…”
Section: Discussionmentioning
confidence: 76%
“…The decision to use this document as a data source is due to the fact that they constitute an official record established by Brazilian legislation. [ 41 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in conducting proper screening for T . gondii infection in risk groups has grown considerably in recent years, as well as the interest in studies to establish some relation to the conditions presented by newborns, such as prematurity and disease severity [ 5 , 18 , 35 42 ].…”
Section: Introductionmentioning
confidence: 99%